Program Pengembangan Santri Cerdas Melalui Pemanfaatan Media Digital Pada Pesantren Nafidatunjannah Gunung Sindur - Dian Nurdiana; Mochamad Bagoes Satria Junianto; Mayang Anglingsari Putri; Denisha Trihapningsari; Irpan Kusyadi (Politeknik Negeri Batam, 2026)
The rapid development of information and communication technology (ICT) has created significant opportunities for Islamic boarding schools (pesantren) to strengthen their roles in education and da'wah in the digital era. Although santri represent a generation that is highly familiar with technology, its use is still predominantly directed toward entertainment rather than self-development or da'wah activities. This study discusses the urgency of technological proficiency among santri, the challenges faced by pesantren in the process of digital transformation, and the importance of guidance to shape santri into positive content creators capable of spreading Islamic values through digital platforms. The main obstacles include limited technological infrastructure, insufficient training for educators, and a lack of understanding of effective digital da'wah strategies. Therefore, this study emphasizes the need to strengthen technological capacity in pesantren through relevant training, adequate ICT facilities, and the development of a digital curriculum aligned with da'wah needs. The findings are expected to serve as a foundation for pesantren in designing effective and sustainable digital transformation programs.